1997
DOI: 10.1073/pnas.94.4.1350
|View full text |Cite
|
Sign up to set email alerts
|

Allergic airway sensitization induces T cell activation but not airway hyperresponsiveness in B cell-deficient mice

Abstract: B cells play an important role in the allergic response by producing allergen-specific Igs as well as by serving as antigen-presenting cells. We studied the involvement of B cells in the development of responses in a murine model of allergic airway sensitization. Normal and B celldeficient ( Mt ؊͞؊ ) B10.BR mice were sensitized via the airways to ovalbumin; Ig production, cytokine elaboration from local lymph node cells, development of airway hyperresponsiveness, and histological changes in the airways were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
97
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(114 citation statements)
references
References 41 publications
15
97
1
Order By: Relevance
“…mMt ±/± mice receiving anti-TNP IgE during 10-day OA nebulization had ES 50 levels similar to those of OA-sensitized, untreated mMt ±/± mice. mice (38). This demonstrates that B cells and/or IgE itself is not essential for allergen-induced T-cell activation and con®rms reports showing B-cell-independent T-cell priming (39), T-cell memory (40,41), and T-cell tolerance (42,43).…”
supporting
confidence: 84%
“…mMt ±/± mice receiving anti-TNP IgE during 10-day OA nebulization had ES 50 levels similar to those of OA-sensitized, untreated mMt ±/± mice. mice (38). This demonstrates that B cells and/or IgE itself is not essential for allergen-induced T-cell activation and con®rms reports showing B-cell-independent T-cell priming (39), T-cell memory (40,41), and T-cell tolerance (42,43).…”
supporting
confidence: 84%
“…Experiments in animals suggest that the early asthmatic response is dependent on antigen-specific IgE (Lambert et al, 1998). Some investigators have suggested that AHR may be dependent on IL-4, which plays a major role in the induction of an IgE response, or on IgE itself (Brusselle et al, 1995;Corry et al, 1996;Hamelmann et al, 1997b). Several reports also indicate that IL-5, which regulates accumulation of eosinophils, plays an important role in AHR and the pathophysiology of changes in the respiratory epithelium (Foster et al, 1996;Hogan et al, 1997a;1998a;Kung et al, 1995;Nakajima et al, 1992).…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10] However, these responses have typically been assessed in isolation from each other. We have recently demonstrated that C57BL/6J mice undergo a biphasic response to aerosolized ovalbumin (OVA) exposure.…”
mentioning
confidence: 99%